2014
DOI: 10.1108/cms-10-2014-0182
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance: institutional arrangement or market choice?

Abstract: Purpose – The purpose of this paper is to investigate the relationship between corporate governance mechanism and firm value of the listed companies in China. Does the better corporate governance lead to the higher firm value? Or does the higher firm value make it easy to choose a better governance mechanism? Or they affect each other? In other words, this paper tries to answer whether the corporate governance mechanism is only decided by institutional arrangement, or by market choice according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Therefore, managerial ownership can decrease moral hazard by the manager (agent) because of the sense of belonging to the company. This result is in line with Ahmed and Nor [12] and Du et al [13] that managerial ownership and firm value affect each other positively.…”
Section: The Relationship Between Managerial Ownership and Firm Valuesupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, managerial ownership can decrease moral hazard by the manager (agent) because of the sense of belonging to the company. This result is in line with Ahmed and Nor [12] and Du et al [13] that managerial ownership and firm value affect each other positively.…”
Section: The Relationship Between Managerial Ownership and Firm Valuesupporting
confidence: 91%
“…This study implies that investors still have reservations about the ability of boards to enhance earnings numbers in Malaysia, although efforts were taken to reform the corporate governance mechanisms following the Asian financial crisis. Du et al [13] found that managerial ownership and firm value affect each other positively. H3: Managerial Ownership has a positive relationship with firm value…”
Section: The Relationship Between Managerial Ownership and Firm Valuementioning
confidence: 99%
“…According to agency theory, concentrated shareholders can monitor corporate operating management effectively, alleviate agency costs and information problems and, consequently, improve firm performance (Blair, 1996;Shleifer and Vishny, 1997). There is also evidence that Dynamic study concentrated shareholders can increase their own benefits at the expense of minority shareholders (Porta et al, 2002;Claessens and Yurtoglu, 2013;Liu et al, 2011;Du et al, 2014). A large body of empirical study has utilized ownership concentration (in the form of either institutional ownership or other block-holder ownership) as a proxy to explore its impact on firm performance (Yu, 2013;Hess et al, 2010;Lin et al, 2009;Gul et al, 2010;Ma et al, 2010;Kang and Kim, 2012;Yixiang, 2011).…”
Section: Ownership Concentrationmentioning
confidence: 99%
“…Previous seminal studies have noted that a high level of managerial ownership contributes to integrating the interests of managers and shareholders and improving firm performance (Jensen and Meckling, 1976;Demsetz and Lehn, 1985). Specifically, there is an alignment of interest when managers are also shareholders (Jiang and Kim, 2015;Du et al, 2014). However, managers also tend to maximize their own benefits, regardless of firm benefits (Fama and Jensen, 1983;Demsetz, 1983), leading to a negative relationship between managerial ownership and firm performance (the "managerial entrenchment" hypothesis).…”
Section: Managerial Ownershipmentioning
confidence: 99%
“…In a word, the institutional change was a result of both institutional arrangement and market selection among shareholders, directors and executives for the sake of their own interests (Du 2014 ). Before the equity division reform at the end of 2006, China's listed companies adopted the equity division of state-owned shares, legal person shares and individual shares.…”
Section: Introductionmentioning
confidence: 99%